Adolescent Resilience and Adversity Quotient in the Digital Age: A Literature Review of Psychological Stress and Adaptive Responses - Fiqri Syahril; Santy Andrianie; Elwas Berdha Krismona; Nor Zaiham Midawati Abdullah (Universitas Negeri Surabaya, 2026)
Adolescents are increasingly exposed to psychological pressures in the digital era, where social media significantly influences identity formation, emotional regulation, and mental well-being. Resilience and Adversity Quotient (AQ) have emerged as two critical psychological capacities that shape adolescents’ ability to cope with stress, failure, and social demands within their environments. This study employs a literature review approach to theoretically examine resilience and AQ among adolescents, aiming to explore their interrelationship and contribution to psychological adaptation. The findings indicate that resilience plays a vital role in emotional recovery, while AQ enables adolescents to interpret adversity as constructive challenges rather than obstacles. The interaction between resilience and AQ forms a protective mechanism that enhances mental health and psychological endurance. This review highlights the importance of educational approaches, family support, and psychological interventions in fostering resilience and AQ as foundational elements for promoting adolescent mental health in the digital era.